Penerapan Aplikasi Stunting Pada Posyandu Kenanga Sebagai Gerakan Masyarakat Sadar Stunting - Handayani, Dwipa; Ardhiyanto, Ozzi; Kusumah, Muhammad Assegaf Raja; Asghor, Ali; Dwidayanto, Ardiansyah; Kurniawan, Kelvin; Nafianto, Dwi; Fadilah, Fikki Arsyi Nur; Pamungkas, Arya Panca; Fadhillah, Muhammad Fahmi; Zahir, Muhammad Rafli Alta (Journal Of Computer Science Contributions (JUCOSCO), 2024)
Stunting, or impaired growth in children, represents a serious and complex global health phenomenon. This article provides a general overview of stunting, encompassing definitions, risk factors, impacts, and prevention efforts. Stunting is closely linked to nutritional aspects, particularly during the first one thousand days of life, including the prenatal period and the first two years of a child's life. Major risk factors involve inadequate nutrition, poor sanitation, and unsupportive socio-economic environments. A profound understanding of stunting, both from health and social perspectives, serves as a foundation for students to engage in prevention and intervention efforts. Students can contribute through community service activities, nutrition education campaigns, and innovative projects aimed at raising awareness about the importance of early nutritional intake. Student involvement at the local level can be pivotal in bridging the gap between science and society, improving access to information, and stimulating behavioral changes. Furthermore, this article highlights the potential of students in the research domain, exploring further knowledge about the underlying factors of stunting and evaluating the effectiveness of existing programs. By integrating students into the stunting prevention agenda, it is hoped that useful and effective programs and applications will be developed to enhance the health of children.